Counsellor Burnout - Yeow, James (INTI Publishing House Sdn Bhd, 2005)
Burnout has been known as “job stress”, ‘battle fatigue”, ‘mental breakdown”, or “premature aging.” All dimensions of our being can manifest burnout, be it psychological or physiological. This paper explores the problem of burnout, which is common in the counselling profession. Physical signs and psychological symptoms can be debilitating to counsellors. The writer presents various theories, which seek to explain the characteristics, causes, consequences, and coping strategies relating to burnout. Three major causes of acute burnout are role conflict, role ambiguity and role overload. Counsellors also experience guilt when their clients commit suicide. Although this research is focused on the concerns of counsellors, the contents and suggestions can be generalized to any practitioner in the human services profession. The ways to reduce burnout include reducing counselling load, implementing a proper referral system, including humor in counselling and so forth. Other strategies are also discussed. Relaxation techniques such as progressive muscle relaxation and guided imagery in music can help when we encounter the early signs of stress. The road to recovery starts with trying to make feelings about our life more explicit and to define some areas and dimensions of life that need renewed energy or redefined commitment. A daily anti-burnout exercise incorporating music therapy is presented in the appendix for the enjoyment of all readers. The key to avoiding burnout is ‘balance”: the word that healthy people live by.